AN ANTHROPOMETRIC STUDY TO ESTABLISH RELATIONSHIP BETWEEN THE UPPER EXTREMITY & STATURE IN MEDICAL STUDENTS BETWEEN THE AGE OF 18 TO 22 YEARS (Journal of Forensic Medicine & Toxicology, 2023)
Physical characteristics that determine the individuality of a person plays a pivotal role in medicolegal investigation. Stature is one of such characteristics which serves as an identification data both in living & dead. In this study 200 medical students (100 males & 100 females) between the age group of 18-22yrs participated in finding the correlation between the stature & measured variables of an upper limb i.e., length & breadth of both hands, length of both middle finger, length of bilateral forearm & length of bilateral arm. The F-ratio in the ANOVA test depicts that the regression coefficient are statistically significant in predicting the stature in females (F (10,89) = 16.073, p
Keywords: Stature; Upper limb; Correlation; Regression